Extended-Release Guanfacine for Hyperactivity in Children With Autism Spectrum Disorder - Scahill, Lawrence; McCracken, James T.; King, Bryan H.; Rockhill, Carol; Shah, Bhavik; Politte, Laura; Sanders, Roy; Minjarez, Mendy; Cowen, Jennifer; Mullett, Jennifer; Page, Chris; Ward, Denise; et al. (The American journal of psychiatry, 2015)
Objective:Hyperactivity, impulsiveness, and distractibility are common problems in children with autism spectrum disorder (ASD). Extended-release guanfacine is approved for children with attention deficit hyperactivity disorder but not well studied in ASD.Method:In a multisite, randomized clinical trial, extended-release guanfacine was compared with placebo in children with ASD accompanied by hyperactivity, impulsiveness, and distractibility.Results:Sixty-two subjects (boys, N=53; girls, N=9; mean age=8.5 years [SD=2.25]) were randomly assigned to guanfacine (N=30) or placebo (N=32) for 8 weeks. The guanfacine group showed a 43.6% decline in scores on the Aberrant Behavior Checklist-hyperactivity subscale (least squares mean from 34.2 to 19.3) compared with a 13.2% decrease in the placebo group (least squares mean from 34.2 to 29.7; effect size=1.67). The rate of positive response (much improved or very much improved on the Clinical Global Impression-Improvement scale) was 50% (15 of 30) for guanfacine compared with 9.4% (3 of 32) for placebo. A brief cognitive battery tapping working memory and motor planning showed no group differences before or after 8 weeks of treatment. The modal dose of guanfacine at week 8 was 3 mg/day (range: 1–4 mg/day), and the modal dose was 3 mg/day (range: 2–4 mg/day) for placebo. Four guanfacine-treated subjects (13.3%) and four placebo subjects (12.5%) exited the study before week 8. The most common adverse events included drowsiness, fatigue, and decreased appetite. There were no significant changes on ECG in either group. For subjects in the guanfacine group, blood pressure declined in the first 4 weeks, with return nearly to baseline by endpoint (week 8). Pulse rate showed a similar pattern but remained lower than baseline at endpoint.Conclusions:Extended-release guanfacine appears to be safe and effective for reducing hyperactivity, impulsiveness, and distractibility in children with ASD.